Ad-hoc Internet Connectivity - Curran, Eoin; Dowling, Jim (Trinity College Dublin, Department of Computer Science, 2003)
For a large class of wireless networks connectivity to fixed services such as the internet will be essential. However, since nodes in a wireless network are mobile, their point of connectivity to a fixed network may be continuously changing. In many cases the route to the fixed network may involve multiple hops across other mobile nodes. This document is an overview of current developments and research in the area of ad-hoc networking and mobility as they relate to the integration of ad-hoc networks with fixed networks.
Keywords: Computer Science